2000
DOI: 10.1021/es991074h
|View full text |Cite
|
Sign up to set email alerts
|

Competition of Ca(II) and Mg(II) with Ni(II) for Binding by a Well-Characterized Fulvic Acid in Model Solutions

Abstract: Competition of Ca(II) and Mg(II) with Ni(II) ions for binding sites of a well-characterized fulvic acid (FA) in model solutions at constant pH and ionic strength was investigated. The Competing Ligand Exchange Method with Chelex-100 and dimethyl glyoxime as the competing ligands was employed to measure the rate of free Ni2+ ion release using graphite furnace atomic absorption spectrometry and adsorptive cathodic stripping voltammetry, respectively. The Windermere Humic Aqueous Model was used to predict the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…The strong association of toxicity with Ni concentrations reflects the occurrence of high Ni concentrations in the highly toxic sediment (and pore water) from Strother Creek. carbonates (Lee et al, 2005) and due to competitive displacement of Ni 2+ from strong binding sites on organic ligands by high concentrations of calcium and magnesium (Mandal et al, 2000). Mandal et al (2002) reported that free Ni 2+ predominated in waters draining another mining area (Sudbury, Canada) that has similar calcium-and magnesium-rich geology.…”
Section: Article In Pressmentioning
confidence: 99%
“…The strong association of toxicity with Ni concentrations reflects the occurrence of high Ni concentrations in the highly toxic sediment (and pore water) from Strother Creek. carbonates (Lee et al, 2005) and due to competitive displacement of Ni 2+ from strong binding sites on organic ligands by high concentrations of calcium and magnesium (Mandal et al, 2000). Mandal et al (2002) reported that free Ni 2+ predominated in waters draining another mining area (Sudbury, Canada) that has similar calcium-and magnesium-rich geology.…”
Section: Article In Pressmentioning
confidence: 99%
“…In earlier studies slow dissociation kinetics 80 of natural Ni-DOM complexes have been demonstrated [6,10,[13][14][15][16], however no data were 81 found on association kinetics. We used the Donnan speciation technique [17], a method which 82 minimizes the disturbance of the equilibrium composition in the test solution and which does 83 not rely on a priori knowledge of the conditional stability constant of a competing ligand.…”
Section: Page 11 Of 31mentioning
confidence: 99%
“…Pertinent studies hitherto published were mostly concerned with the displacement of divalent trace metals (Ni, Cu, Zn, Cd, Pb) by calcium or magnesium (e.g., Buffle et al, 1980;Hering and Morel, 1988;Cabaniss and Shuman, 1988;Cao et al, 1995;Van den Hoop et al, 1995;Mandal et al, 2000), several papers dealt with the competitive effect of aluminium (e. g., Susetyo et al, 1990;Pinheiro et al, 2000;Lippold et al, 2005). There are only few investigations on the influence of iron(III), although it is the most abundant trivalent electrolyte in terrestrial waters, and expected to be very effective in out competing other metals.…”
Section: Introductionmentioning
confidence: 99%